Students' and teachers' perceptions of English Day program: A case at an Acehnese School - Tathahira Tathahira; Sriayu Nahrisya (ACCENTIA: Journal of English Language and Education, 2020)
This study investigated the perceptions of students and teacher toward the implementation of English Day program. The study took place at SMAS Insan Madani, Meukek Sub-district, South Aceh District, Aceh, Indonesia. English Day is a program commonly conducted in most integrated schools in Indonesia which aims to promote students’ English speaking activities. The study used qualitative research methods, collecting data from interview. Participants of the study included four students and one teacher involved in English Day program. The results of the study showed that English Day was quite an enjoyable learning environment for the students to practice English. Still, the students felt sometimes discouraged due to some psychological factors. Nevertheless, the teacher had been supportive in the program and also provided necessary feedback for the students.